2019
DOI: 10.1111/dom.13809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the mineralocorticoid receptor antagonist eplerenone on liver fat and metabolism in patients with type 2 diabetes: A randomized, double‐blind, placebo‐controlled trial (MIRAD trial)

Abstract: Aim To investigate whether the mineralocorticoid receptor antagonist eplerenone has beneficial effects on liver fat and metabolism in patients with type 2 diabetes (T2D), the mineralocorticoid receptor antagonist in type 2 diabetes (MIRAD) trial. Material and methods In this 26‐week, double‐blind, randomized, placebo‐controlled trial, we enrolled 140 patients with T2D and high risk of cardiovascular disease. Patients were randomized 1:1 to either eplerenone with a target dose of 200 mg/day for patients with es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…The beneficial impact of the MRA-induced reduction in Col-6 expression in the current study is supported by an experimental study that reported that elimination of Col-6 is linked with normalized adipose tissue structure and improved metabolism (1). The clinical implications of the reduced fibrosis in ScAT in patients with type 2 diabetes are yet to be determined since we did not demonstrate an effect of eplerenone on liver fat in the MIRAD trial (13). A human study reported an impact of increased pericellular fibrosis in ScAT on weight loss after bariatric surgery, thus suggesting a link with obesity (2).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The beneficial impact of the MRA-induced reduction in Col-6 expression in the current study is supported by an experimental study that reported that elimination of Col-6 is linked with normalized adipose tissue structure and improved metabolism (1). The clinical implications of the reduced fibrosis in ScAT in patients with type 2 diabetes are yet to be determined since we did not demonstrate an effect of eplerenone on liver fat in the MIRAD trial (13). A human study reported an impact of increased pericellular fibrosis in ScAT on weight loss after bariatric surgery, thus suggesting a link with obesity (2).…”
Section: Discussionsupporting
confidence: 66%
“…The study population consisted of patients with type 2 diabetes enrolled in the MIRAD study, which was a 26-week, randomized, double-blind, placebo-controlled trial that investigated the effects of high-dose eplerenone on liver fat content in patients with type 2 diabetes (13). All patients were proposed to participate, with an aim of including 30 in this prespecified substudy.…”
Section: Study Populationmentioning
confidence: 99%
“…This might be due to the ability of lipoproteins and of adipocyte-derived factors, such as leptin, to induce the adrenal synthesis of aldosterone [42][43][44][45]. In patients with primary aldosteronism, treatment through pharmacological MR antagonists (MRA) (eplerenone or spironolactone) or adrenalectomy reduces visceral fat mass [46] and improves systemic and organ insulin sensitivity [47], but other studies have shown only limited effects of MRA in obese diabetic patients [48][49][50]. The reason for these diverging results could be that MRA are often used as a preventive treatment in mice, while human studies are done in patients that are already suffering from the MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional studies investigating the effect of MRAs on liver fat have yielded inconsistent findings. Polyzos et al reported a significant improvement in liver fat score over 1 year in 31 subjects with biopsy-proven non-alcoholic fatty liver disease randomised to spironolactone (25 mg daily) plus vitamin E compared to vit E alone [68], while in a recent randomised controlled trial by Johansen et al involving 140 patients with longstanding type 2 DM (80% of whom were already on angiotensin receptor blocker or angiotensin converting enzyme inhibitor treatment), there was no change in liver fat after 26 weeks of treatment with eplerenone (50-200 mg daily) [69].…”
Section: Do the Metabolic Effects Of Mr At Tissue Level Translate Intmentioning
confidence: 99%